Implementation Of Decision Selection In The Selection Of Transportation Modes Among Workers And Students In Medan City Using Ahp And Electric Methods - Sabrina, Ladia; Rakhmawati, Fibri; Husein, Ismail (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
The mode of transportation is a means of connecting used by workers and students to be able to help with all daily activities. The development of transportation modes is increasingly significant with the addition of wider technological sophistication, so that there are more and more diverse types of transportation modes. The purpose of this research is to determine the factors that have the most influence on the choice of mode and provide more effective decisions among workers and students in the selection of public transportation modes to be used. In this research, the decision support system (DSS) method is used, namely the analytical hierarchy process (AHP) and elimination et choix traduisant la reality (ELECTRE) by performing multi-criteria calculations that compare the criteria and alternatives. Where the results obtained in this research is that the most influential factor in the selection of transportation modes among workers is time efficiency with a weight of 25.9 %, while the influential factor for students is cost which produces a weight of 30.7 %. The most effective and efficient alternative mode of transportation among workers is Go-Jek Bike, while for students it is Transmetro Deli.